UPAYA PENINGKATAN KOMPETENSI MEMBACA GAMBAR PADA KOMPETENSI DASAR GAMBAR PROYEKSI DENGAN MEDIA VISUAL BERBASIS KOMPUTER DI PROGRAM STUDI TEKNIK PEMESINAN SMK NEGERI 2 KARANGANYAR TAHUN PELAJARAN 2014/2015 - Putra, Ratna (Jurnal Nosel, 2016)
The purpose of this research is to improve the competence of students in engineering drawing for X Enginering B grade students of Vocational High School Satate 2 Karanganyar by using computer-based visual media. This research is a classroom action research. The research conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. The subjects are X Enginering B grade students of Vocational High School Satate 2 Karanganyar totaling 35 students. Source data come from teachers and students. Data collection techniques in this study are the observation, documentation and testing. Data analysis technique used is descriptive comparative. Research procedures are interrelated spiral model. The results showed that the application of computer-based visual media can enhance the competence to read engineering drawings X Enginering B grade students of Vocational High School Satate Negeri 2 Karanganyar academic year 2014/2015. This is evidenced by the growing of students competence which seen from the student record before and after the implemented action research. The average value of the X Enginering B grade students in the initial conditions is 63,66 with the number of graduate students as many as 13 or 37% of the total as many as 35 students. The average value of students in the first cycle is 73,54 by the number of graduate students as many as 22 or 9 students more than ever, an increase of 26% and a graduation rate to 63%. Furthermore, the graduation rate of students in the second cycle increased by 20% from the previous so as to 83% or a total of 29 students who graduated with an average of 73,29. The conclusions of this research is the application of computer-based visual media can improve reading competence engineering drawings X Enginering B grade students of Vocational High School State 2 Karanganyar.